AGGRESSIVE BEHAVIOR PATTERN, CHARACTERISTICS AND FANATICISM PANSER BIRU GROUP PSIS SEMARANG (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
This research aim to find out about 1) the aggressive behavior pattern posed by supporters Panser Biru and see how 2) the role of supporters of the PSIS Semarang, 3) understanding the Panser Biru PSIS Semarang fans about the meaning of fanaticism against PSIS club, 4) characteristics of groups Panser Biru PSIS Semarang, 5) the impact of aggressive behavior caused by the Panser Biru PSIS Semarang Supporters on the surrounding community. This study used a qualitative approach. The population was Panser Biru PSIS Semarang Supporters Group and the sample was taken from several Korwil were 30 respondents, data collection technique was participant observation, depth interviews, document searches, and triangulation of data. The data obtained were analyzed qualitatively by following these steps: 1) data reduction, 2) presentation of data, and 3) conclusion. This research has resulted that 1) the pattern of aggressive behavior that arises in the group of supporters made collectively Panser Biru PSIS Semarang is the result of frustration-aggression caused aggressive behavior types (a) physical aggression and (b) verbal aggression. 2) understanding the fanaticism of panser biru supporters groups are situational to support PSIS, the behaviors that are beyond irrational will appear when their beloved team being hurt or harmed other teams, depending on the team that faced by PSIS, 3) the role is seen from the Panser Biru PSIS Semarang fans only limited to members of support and motivation to PSIS Semarang, 4) characteristic of panser biru supporters that is they move through small groups in groups to form a crowd within powerful cohevitas and collective behavior, from blue sedge dominant attributes and have special slogans, 5) impact of aggressive behavior is panser biru supporters groups in terms of economic benefits to traders about, for PSIS was uncomfortable with verbal aggressive behavior that often occurs in every game .This study concludes: 1) aggressive behavior patterns that arise in groups of supporters be done collectively Panser Biru is frustration-aggression, 2) the role of Panser Biru supporters as advocates and sources of material for PSIS, 3) understanding fanaticism of panser biru blue situational fans to support the PSIS, 4) characteristics of a Panser Biru supporters group is the attribute is blue and has a chant for PSIS, 5) the impact on the communities that benefit economically while for the PSIS team players feel uncomfortable with the aggressive behavior that posed, especially verbal aggression that is often sung at every game.